2018
DOI: 10.1016/j.bbadis.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of astrocyte function in neuroinflammation and neurodegeneration

Abstract: Epigenetic mechanisms control various functions throughout the body, from cell fate determination in development to immune responses and inflammation. Neuroinflammation is one of the prime contributors to the initiation and progression of neurodegeneration in a variety of diseases, including Alzheimer's and Parkinson's diseases. Because astrocytes are the largest population of glial cells, they represent an important regulator of CNS function, both in health and disease. Only recently have studies begun to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 196 publications
0
80
0
Order By: Relevance
“…[57][58][59][60] Alteration of DNA methylation has been implicated in We observed that WMI induced methylation perturbation in a period highly important for neurodevelopment that persisted up to 21 days post-injury.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[57][58][59][60] Alteration of DNA methylation has been implicated in We observed that WMI induced methylation perturbation in a period highly important for neurodevelopment that persisted up to 21 days post-injury.…”
Section: Discussionmentioning
confidence: 79%
“…DNA methylation is an important regulatory mechanism that partakes in neurodevelopmental processes, different neurological functions such as learning and memory and maintenance of homeostasis at adulthood. [57][58][59][60] Alteration of DNA methylation has been implicated in…”
Section: Discussionmentioning
confidence: 99%
“…; Chitnis and Weiner ; Labzin et al . ; Fehily and Fitzgerald ; Mizuma and Yenari ; Neal and Richardson ; Franklin et al . ; Prata et al .…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…The disorders considered in the present review are caused by different etiologic factors and display a variety of symptoms that could hardly be reconducted to a unifying pattern. However, regardless of the origin of these diseases, the involvement of processes which share aspects reasonably attributable to inflammation is detectable in their underlying pathogenic mechanisms (Giovannoni et al 2007;Wilcock and Griffin 2013;King et al 2014;Ochoa-Cortes et al 2016;Hamlett et al 2018;Stark et al 2016;Chitnis and Weiner 2017;Labzin et al 2018;Fehily and Fitzgerald 2017;Mizuma and Yenari 2017;Neal and Richardson 2017;Franklin et al 2017;Prata et al 2017;Santos and Ferreira 2017;Joshi and Singh 2017;Thelin et al 2017a;Majd et al 2017;Zhang et al 2017;Zolezzi and Inestrosa 2017). This consideration has also been the object of a recent valuable review (Skaper et al 2018).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Neurodegenerative diseases are characterised by a progressive decline in neuronal health ultimately leading to cell death. Alzheimer's (AD), Parkinson's (PD) and Huntington's diseases are increasingly prevalent neurological conditions that share several common pathways including neuroinflammation, enhanced oxidative stress, metabolic dysfunction and most importantly, the accumulation of misfolded proteins [1][2][3]. One particular form of neuronal degeneration caused by propagating protein misfolding is prion disease, a fatal, progressive neurodegenerative disorder characterised by an accumulation and aggregation of misfolded scrapie-like prion protein PrP Sc [4,5].…”
Section: Mainmentioning
confidence: 99%